Detecting GPC3-Expressing Hepatocellular Carcinoma with L5 Peptide-Guided Pretargeting Approach: In Vitro and In Vivo MR Imaging Experiments. (10th September 2018) - Li, Weiyue; Xiao, Xiang; Li, Xiaodan; Xu, Yikai; Ma, Lichao; Guo, Liuji; Yan, Chenggong; Wu, Yuankui
Abstract : Objective . To investigate the potential of L5 peptide-guided pretargeting approach to identify GPC3-expressing hepatocellular carcinoma (HCC) using ultrasmall superparamagnetic iron oxide (USPIO) as the MR probe. Methods . Immunofluorescence with carboxyfluorescein- (FAM-) labeled L5 peptide was performed in HepG2 cells. Polyethylene glycol-modified USPIO (PEG-USPIO) and its conjugation with streptavidin (SA-PEG-USPIO) were synthesized, and their hydrodynamic diameters, zeta potential, T2 relaxivity, and cytotoxicity were measured. In vitro and in vivo two-step pretargeting MR imaging was performed on HepG2 cells and tumor-bearing mice after the administration of biotinylated L5 peptide (first step), followed by SA-PEG-USPIO (second step). Prussian blue staining was performed to assess iron deposition in tumors. Results . The high specificity of L5 peptide for GPC3 was demonstrated. Generation of SA-PEG-USPIO nanoparticles with good biocompatibility (an average hydrodynamic diameter of 35.97 nm and a zeta potential of −7.91 mV), superparamagnetism ( R 2  = 0.1039 × 10 3  mM −1 s −1 ), and low toxicity was achieved. The pretargeting group showed more enhancement than the nonpretargeting group both in vitro (60% vs 20%, P < 0.05 ) and in vivo (32% vs 6%, P < 0.001 ). Substantial iron deposition was only observed in HepG2 cells and tumors in the pretargeting group. Conclusion . L5 peptide-guided, two-step pretargeting approach with USPIO as the MR imaging probe is a lucrative strategy to specifically identify GPC3-expressing HCC.